Estrogen replacement improves verbal memory and executive control in oligo-amenorrheic athletes in a randomized controlled trial - Baskaran, Charu (J Clin Psychiatry, 2017)
OBJECTIVE: Both estrogen and exercise may have cognition enhancing benefits; however, young oligo-amenorrheic athletes (OA) with estrogen deficiency have not been evaluated for cognitive deficits. Our objective was to determine whether 6 months of estrogen replacement will impact cognitive domains in OA. We hypothesized that estrogen replacement would improve verbal memory (VM) and executive control in OA. METHODS: We performed cognitive assessments at baseline and after 6 months in 48 OA (14–25 years) randomized to estrogen (EST+) (oral 30 mcg ethinyl estradiol (n=16) or transdermal 100 mcg 17-beta-estradiol patch (n=13)), or no estrogen (EST-) (n=19) in an ongoing clinical trial. Neurocognitive testing included California Verbal Learning Test II (CVLT-II) (for VM), and Delis-Kaplan Executive Function System Color-Word Interference Test (D-KEFS-CWIT) (executive control). RESULTS: On average, subjects (age: 19.9±3.1 years, BMI: 20.6±2.3 kg/m(2)) participated in 10.3±5.9 hours/week of weight-bearing activities of lower limbs. The EST+ group performed better for CVLT-II VM scores for immediate recall over 6 months of therapy compared to EST- (p<0.05) even after controlling for baseline scores and age. Changes in D-KEFS-CWIT over 6 months did not differ between the groups. However, the EST+ group had greater improvements in inhibition-switching completion time over 6 months compared with the EST- group after controlling for baseline scores and age (p=0.01). CONCLUSION: OA show improvements in VM and executive control following 6 months of estrogen replacement. These findings in athletes, who are in their prime of neurocognitive development, underscore the need for future studies exploring cognition in OA.